AB1371 Severity of incident vertebral fracture and future fracture risk: A 3-year prospective study. (23rd January 2014) - Bruyere, O.; Roux, C.; Nicolet, D.; Fechtenbaum, J.; Deroisy, R.; Reginster, J.-Y.
Abstract : Objectives: To examine whether the severity of an incident vertebral fracture can predict subsequent fracture. Methods: Analysis from the placebo group of two 3-year randomized controlled trials investigating the clinical effect of an anti-osteoporotic drug. Vertebral and major non-vertebral fractures (i.e. ribs sternum, wrist region, pelvic sacrum, collarbone, humerus, proximal femur) were assessed during 3 years. At the end of the first year, each vertebra received a severity grade corresponding to either no fracture either a mild, moderate or severe fracture based on a semi-quantitative visual assessment on standard radiographs. All women received calcium and vitamin D during the 3 years of the study. Results: 2550 women aged mean (SD) 74.4 (6.1) years were included in the present analysis. After one year of follow-up, 6.9% of the women (n=271) experienced a new vertebral fracture. Among these new fractures, 47.8% were mild, 30.9% were moderate and 21% were severe. During the following two years of follow-up (i.e. years 2 and 3), 410 patients experienced a new vertebral fracture. Among women with an incident vertebral fracture at year 1, 28.0% experienced a new vertebral fracture during years 2 and 3. However, this rate of new fracture was only 15.4% among women without incident vertebral fracture during the first year of follow-up. Compared to women without new vertebral fracture after one year of follow-up, women who experienced a severe fracture during year 1 have an increased risk of new vertebral fractures during the following two years (OR 2.39 [1.56-3.67]). When considering major non-vertebral fracture, 149 subjects experienced such fractures during year 2 and 3. Women who experienced a severe vertebral fracture during the first year have an increased risk of major non-vertebral fractures during the following two years compared to women without incident vertebral fracture after one year of follow-up (OR 2.31 [1.01-5.32]). Conclusions: New severe incident vertebral fracture is an independent predictor of new vertebral and non-vertebral fractures that could be taken into account in fracture risk management. Disclosure of Interest: None Declared